Review on Microscale Sensors with 3D Engineered Structures: Fabrication and Applications. Issue 4 (27th January 2022) - Zhang, Cheng; Qu, Menglong; Fu, Xiuqing; Lin, Jian
Abstract: The intelligence of modern technologies relies on perceptual systems based on microscale sensors. However, because of the traditional top‐down fabrication approaches performed on planar silicon wafers, a large proportion of existing microscale sensors have 2D structures, which severely restricts their sensing capabilities. To overcome these restrictions, over the past few decades, increasing efforts have been devoted to developing new fabrication methods for microscale sensors with 3D engineered structures, from bulk chemical etching and 3D printing to molding and stress‐induced assembly. Herein, the authors systematically review these fabrication methods based on the applications of the resulting 3D sensors and discuss their advantages compared to their 2D counterparts. This is followed by a perspective on the remaining challenges and possible opportunities. Abstract : Comprehensively and accurately perceiving the physical world relies on sensory systems built on microscale sensors. The microscale sensors with 3D engineered structures possess many advantages such as high sensitivity, spatial resolution, conformity, and multimodality. In this review, fabrication methods and applications of the 3D sensors are systematically summarized, followed by a perspective on the remaining challenges and possible opportunities.